Mapping and sectoral analysis of inventory management techniques: a comparative approach between traditional and modern methods - Nunes, Iza Maria da Silva; Silva, Yuri Laio Teixeira Veras (Brazilian Journal of Production Engineering, 2026)
Efficient inventory management is essential to organizational performance, motivating the search for methods that improve control and reduce operating costs. In this context, this study presents the mapping and comparative analysis of 12 inventory techniques (six traditional and six modern), providing a clear overview of the approaches and their applications across different sectors. The results indicate that traditional techniques remain widely used in retail, distribution, and manufacturing due to their simplicity and ease of integration into existing processes, whereas modern techniques, driven by technological advances, have spread mainly in logistics, technology, and more digitized industries because of their potential to increase accuracy and responsiveness. The comparison between the groups highlights relevant differences in complexity, required technological support, and suitability for distinct production contexts. It is concluded that the evolution of these techniques is continuous and essential to operational efficiency, offering support for companies to choose the approach best suited to each sector’s needs.